Etika Keutamaan dalam Arah Pendidikan Indonesia Kontemporer - Johanis Ohoitimur (Respons: Jurnal Etika Sosial, 2016)
Virtue ethics as developed by Aristotle focuses on self development in a sense that right or wrong will be measured by the virtue which is needed for the excellence of the human person. Tere are many virtues, but the most fundamental is phronesis. Every body who has phronesis will act according to rational judgement. It is based on what is good and what is right for the development of human beings. Tis article tries to explicate the thesis that the national system of education in elementary school and high school which focuses on the character building is in line with virtue ethics. In this afnity, knowledge and practical skill get their meaning in the frame of character building. As Aristotle convinced that both phronesis and character can be formed through habituation, it suggests that habituation is the only way to enhance the moral and value education.Character, education, phronesis, selft development, virtueEtika keutamaan, seperti yang menjadi pendirian Aristoteles, menekankan pengembangan diri. Manusia yang benar dan baik diukur menurut keutamaan yang dimiliki. Ada banyak keutamaan, tetapi yang terpokok ialah kebijaksanaan dalam arti phronēsis. Orang yang memiliki phronēsis bertindak menurut pertimbangan yang bijaksana dan berorientasi pada apa yang benar dan baik bagi manusia. Artikel ini berusaha melakukan eksplisitasi bahwa arah pendidikan nasional pada jenjang pendidikan dasar dan menengah menekankan dan fokus pada etika keutamaan, yaitu pembentukan karakter atau watak peserta didik. Pengetahuan (kognitif) dan keterampilan praktis (psikomotorik) mendapatkan coraknya dari karakter. Sama halnya dengan kebijaksanaan praktis (phronēsis) dalam ajaran Aristoteles, karakter hanya bisa dibentuk melalui pembiasaan bertindak atau berperilaku. Dalam konteks ini pendidikan nilai dan pendidikan moral menemukan jalannya.Etika keutamaan, pengembangan diri, phronesis, pendidikan, karakter